Functions
In this tutorial, you will learn the following in detail:
- Functions
- Composite Functions
- Inverse Functions
Functions
y = x2 + 3x -2 is said to be a function of x - an expression of x. This can also be written, in a bit more advanced way as f(x) = x2 + 3x -2 -
it is read as you write, function of x, f(x)
So, f(x) = x2 + 3x -2
Now whatever you put in as 'x' on the left, substitutes 'x' on the right.
E.g.
- f(2) = 22 + 3x2 -2 = 4 + 6 - 2 = 8
- f(-2) = (-2)2 + 3x(-2) -2 = 4 - 6 - 2 = -4
- f(0) = 02 + 3x0 -2 = 0 + 0 - 2 = -2
- f(x+1) = (x+1)2 + 3(x+1) -2 = x2 + 2x + 1 + 3x + 3 -2 = x2 + 5x + 2
- f(x-1) = (x-1)2 + 3(x-1) -2 = x2 - 2x + 1 + 3x - 3 -2 = x2 + x - 5
- f(2x) = (2x)2 + 3(2x) -2 = (2x)2 + 6x -2 = 4x2 + 6x - 2
- f(x/2) = (x/2)2 + 3(x/2) -2 = x2/4 + 3x/2 -2 = x2/4 + 3x/2 - 2
- f(x²) = (x²)² + 3(x²) - 2 = x4 + 3x² -2
Composite Functions
A function of a function is called a composite function.
E.g.1
f(x) = 2x-1 | g(x) = x²
fg(x) = 2(x²) -1
gf(x) = (2x-1)²
f²(x) = ff(x) = 2(2x-1) - 1 = 4x - 2 - 1 = 4x - 3
g²(x) = gg(x) = (x²)² = x4
E.g.2
f(x) = 3x-2 | g(x) = x² | h(x) = (x + 3)/2
Find fgh(x)
gh(x) = [(x+3)/2]² = (x+3)²/4
fgh(x) = ff(x) = 3(x+3)²/4 - 2
E.g.3
f(x) = 3x | g(x) = x² | h(x) = x-1
Find gfh(x)
fh(x) = 3(x-1) = 3x - 3
gfh(x) = (3x - 1)²
E.g.4
f(x) = 3x-1 | g(x) = x² - 2x
Find gf(1)
f(1) = 2
gf(1) = 1² -2(1) = -1
E.g.5
f(x) = 3x-2 | g(x) = 2x + 7
If gf(b) = 21, find b.
gf(x) = 2(3x - 2) + 7 = 6x - 4 + 7 = 6x + 3
gf(b) = 6b + 3
6b + 3 = 21
6b = 18
b = 3
Inverse Functions - f-1(x)
If two functions exist in such a way that the input of one of them is the output of the other or vice versa, they are a function and its own inverse.
E.g. g(x) = 2x- 3; -2 ≤ x ≤ 3
x |
g(x) |
-2 |
-7 |
-1 |
-5 |
0 |
-3 |
1 |
-1 |
2 |
1 |
3 |
3 |
E.g. h(x) = (x + 3)/2; -7 ≤ x ≤ 3
x |
h(x) |
-7 |
-2 |
-5 |
-1 |
-3 |
0 |
-1 |
1 |
1 |
2 |
3 |
3 |
Since the above two functions swap around their input and output, they are a pair of a function and its inverse.
If f(x) = 2x - 3, then f-1(x) = (x + 3)/2 and vice versa.
Turning a function into its inverse function
Method 1
Method 2
- Swap x and y around.
- Make y the subject.
E.g.
f(x) = 2x - 3
y = 2x - 3
Swapping x and y around,
x = 2y - 3
y = (x + 3)/2
f-1(x) = (x + 3)/2
Important facts about an inverse function
- ff-1(x) = f-1f(x) = x
- The function and its inverse are symmetrical in the y = x line.
Practice Questions
- y = -3x + 2
- y = 2 + 3(x + 1)
- y = 3 - 2(4x + 1)
- y = 1/(x - 2)
- y = 3 - 2x/3
- y = x² - 3
- If f(x) = 2x - 7, solve f-1(x).
- If f(x) = 3 + 2(x - 3), solve f-1(x).
- if f(x) = 2x + 1 and g(x) = x², solve fg(x) = gf(x).
- If f(x) = 4x - 3 and g(x) = x/3, solve f-1(x) = g-1(x).
Answers
Move the mouse over, just below this, to see the answers:
- y = (2-x)/3
- y = (x-2)/3 - 1
- y = (1 - x)/8
- y = 1/x + 2
- y = 3(3 - x)/2
- y = √(x+3)
- x = 7
- x = 3
- x = 0 and x = -2
- x = 0.27
Now that you have read this tutorial, you will find the following tutorials very helpful too: